ANALISIS YURIDIS RANGKAP JABATAN DIREKTUR PT SHOPEE INTERNATIONAL INDONESIA DAN PT NUSANTARA EKSPRES KILAT - NIM. A1011211278, ELVI TURSINA FIRANTI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Interlocking directorates by the Director of PT Shopee International Indonesia and PT Nusantara Ekspres Kilat violates Article 26 of Law No. 5 of 1999 due to indications of unfair business competition during the interlocking directorate period. According to investigation by the Indonesian Competition Commision (KPPU), Shopee has discriminately prioritized its internal delivery service, Shopee Express. It was demonstrated that this interlocking directorates act is affecting the policies of businesses, which consequently had an impact on competition within the respective market. Article 26 of Law No. 5 of 1999 does not impose an absolute prohibition on holding interlocking directorates act itself, but it mandates an analysis to determine if such roles lead to monopolistic practices and/or unfair business competition. The type of research conducted is normative juridical with descriptive analysis, using the rule of reason approach and case approach. The data was collected using technique involves literature research, then analyzed by interpreting Law No. 5 of 1999 in relation to the behavior of interlocking directorates by the director in PT Shopee International Indonesia and PT Nusantara Ekspres Kilat. There are indication that the interlocking directorates by the Director of PT Shopee International Indonesia and PT Nusantara Ekspres Kilat violates Article 26 of Law No. 5 of 1999. This interlocking directorates is to result in significant legal implications for the policies implemented on the Shopee platform. Shopee is alleged to have engaged in discriminatory practices in selecting delivery services on its platform, which constitutes a violation of Article 19 letter (d) of Law No. 5 of 1999. KPPU conducted its first hearing concerning Shopee